The Geo-educational and Conservational Challenges Posed by Unconsolidated Deposits: Some Thoughts and Possible Solutions as Applied to Diamicton Deposits from the British Isles - Murphy Phillip (Geoconservation Research)
Unconsolidated diamicton deposits of Quaternary age cover much of the lowland areas of the British Isles. These are often poorly exposed and as a result their influence on development and importance as palaeontological archives are often under appreciated. Maintaining exposures in such strata is often challenging and their incorporation into the built environment is limited and is biased towards larger particles sizes and more indurated lithologies. The use of gabions is suggested as a possible solution to ensuring such geo-materials can be made available for educational use.